The Characteristics of Teacher Leadership Behaviour in the Class of Physical Health Education (PJOK) at SMA Negeri 1 Simpang Tiga from the Academic Year 2020/2021 - Amirzan Amirzan; Ilyas Ilyas; Muhammad Muhammad; Herizal Herizal; Husaini Abdullah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research aims to investigate the extent to which the system or leadership style is owned and implemented by Physical Health Education (PJOK) teachers when they teach the students, both theoretical and practice, this is important because success in teaching is strongly influenced by various factors, one of which is the teacher attitude as behavior in the implementation of educational learning which is often referred to as a model or lead character. The data for this qualitative study derives from a questionnaire to 26 respondents namely, school leaders, school administration, students and PJOK teachers in SMA Negeri I Simpang Tiga. While the research question posed is "What type of leadership characteristics are generally the most dominant adopted or implemented by PJOK teachers at SMA Negeri I Simpang Tiga". Based on the results of data processing in the questionnaire, it can be concluded that in general the PJOK teachers at SMA Negeri I Simpang Tiga have implemented a "democratic" leadership type in nature.